Mobile money and women empowerment in Sub-Saharan Africa: an exploratory study - Poiret, Juliette Clemence (2016)
This research explores the relationship between the penetration of mobile money services and the state of women empowerment across 30 Sub-Saharan African countries. Our purpose is to determine whether fostering the development of mobile money can be a useful tool to reinforce women empowerment in developing countries. We perform an exploratory data analysis, as well as correlation and regression analyses, to assess the effect of mobile money services on women empowerment. In order to do that, we construct several mobile money variables and a women empowerment index, using national-level data collected through questionnaires addressed by the World Bank on selected samples. Our results show a positive yet moderate relationship, and pave the way for further research on this subject.